2020
DOI: 10.3857/roj.2020.00094
|View full text |Cite
|
Sign up to set email alerts
|

The effect of deep inspiration breath-hold technique on left anterior descending coronary artery and heart dose in left breast irradiation

Abstract: To determine the effect of the deep inspiration breath-hold (DIBH) technique on left anterior descending coronary artery (LAD) region and heart dose in left breast cancer irradiation. Materials and Methods: Twenty-five left breast cancer patients who previously received breast-conserving surgery underwent computed tomography (CT) simulation with both free-breathing (FB) and DIBH techniques and four radiation treatment plans. The plan comprised the following with both the FB and DIBH techniques: whole breast (W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 21 publications
2
14
0
1
Order By: Relevance
“…Neste estudo, a unidade 1 ficou próximo ao limite determinado, entretanto os demais casos permaneceram em um nível significativamente a abaixo. Com exceção da unidade 1, o achado deste estudo foi condizente com Sakyanun et al (2020) que em seu estudo obteve o V25Gy de 2,9%.…”
Section: Resultsunclassified
“…Neste estudo, a unidade 1 ficou próximo ao limite determinado, entretanto os demais casos permaneceram em um nível significativamente a abaixo. Com exceção da unidade 1, o achado deste estudo foi condizente com Sakyanun et al (2020) que em seu estudo obteve o V25Gy de 2,9%.…”
Section: Resultsunclassified
“…Several studies ( 20 , 21 , 26 ) have demonstrated that the maximum heart distance (MHD) is a good predictor of the mean heart dose. The MHD was measured as the maximum width of the heart in the tangent fields.…”
Section: Discussionmentioning
confidence: 99%
“…The DIBH method is capable to reduce the dose to the heart, LAD and RCA. 28,29 Nevertheless, this practice might not be achievable for all patients. Holding the breath for a few minutes is a difficult task for certain patients.…”
Section: Discussionmentioning
confidence: 99%